The trace of the English children’s books in the first series of «Cuentos de Calleja en colores» - Fraga, María Jesús; Urdiales, Alberto (Escritura e Imagen, 2019)
Between 1916 and 1917, the publisher Saturnino Calleja, published the first three series of his collection «Cuentos de Calleja en colores». This article explores the English origins of most of his texts, illustrations and formats. Although the original illustrations of the first series were replaced by others made by Spanish avant-garde artists, the second and third come in full from original English editions purchased beforehand.
Keywords: Calleja Publisher; Cuentos de Calleja en colores; illustrators; English edition; translaters